ESTIMATION OF BODY WEIGHT FROM DIFFERENT MORPHOMETRIC MEASUREMENTS IN KAJLI LAMBS - Z. M. Iqbal; K. Javed; M. Abdullah; N. Ahmad; A. Ali; A. Khalique; N. Aslam; U. Younas (Journal of Animal and Plant Sciences, 2014)
Data were collected on 214 Kajli lambs (109 females and 105 males) of different age groups maintained at Livestock Experiment Station Khizrabad (Sargodha) Pakistan. The animals were divided into three age groups as 0-3, 4-6 and 7-9 months. Within each group, the data on male and female lambs were collected separately. To predict the weight of Kajli sheep three body measurements (wither height, body length and heart girth) were recorded on each animal. Body measurements varied with increasing age of animals. In male lambs, the highest correlation (r2) was observed between body weight and heart girth at 0-3 (r2 =0.86) and 4-6 (r2 =0.91) months of age, while in females the highest relationships 0.79 and 0.80 were observed between body weight & heart girth at 0-3 months and body weight & body length at 4-6 months of age, respectively. These correlations between body weight and body measurements were positive and significant (P<0.05). The regression analysis indicated that live weight and body measurements (wither height, body length and heart girth) had linear relationship (P-value = 0.0001, 0.0001 and 0.0001) at 0-3 month of age. During present investigation, males were found heavier (P<0.05) and longer (P<0.05) than females in the first two age groups. Similarly, in the first age group, the height at withers was higher (P<0.05) in males than in females. In male Kajli lambs, The coefficient of determination (R2) for weight estimation were for body length and height at wither (74.2%) at 4-6 month, while in female the higher value of R2 was observed between height at wither and heart girth (89.0%) at 4-6 month of age. It was concluded that body weight of Kajli lambs can be estimated in field using morphometric measurements taken with a tape in the absence of weighing scales.
Keywords: lambs; body; height; wither; heart; girth; weight